2016
DOI: 10.3389/fmars.2016.00244
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Respiration Rates in Water with Sub-Micromolar Oxygen Concentrations

Abstract: It is crucial for our study and understanding of element transformations in low-oxygen waters that we are able to reproduce the in situ conditions during laboratory incubations to an extent that does not result in unacceptable artifacts. In this study, we have explored how experimental conditions affect measured rates of O 2 consumption in low-O 2 waters from the anoxic basin of Golfo Dulce (Costa Rica) and oceanic waters off Chile-Peru. High-sensitivity optode dots placed within all-glass incubation container… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 29 publications
5
25
0
Order By: Relevance
“…a,b). A similar acceleration during batch incubation has been observed for other microbial processes in OMZs and is generally considered as a “bottle effect” with the initial rates assumed to reflect in situ activity more accurately than rates during the acceleration period (e.g., Thamdrup et al ; Garcia‐Robledo et al ). Accordingly, all rates and rate constants reported here are based on 24 h incubations.…”
Section: Resultsmentioning
confidence: 63%
“…a,b). A similar acceleration during batch incubation has been observed for other microbial processes in OMZs and is generally considered as a “bottle effect” with the initial rates assumed to reflect in situ activity more accurately than rates during the acceleration period (e.g., Thamdrup et al ; Garcia‐Robledo et al ). Accordingly, all rates and rate constants reported here are based on 24 h incubations.…”
Section: Resultsmentioning
confidence: 63%
“…Good agreement was found between measurements of oxygen concentration and oxygen consumption made by STOX sensors, optode spots and membrane inlet mass spectrometric analysis of 18−18 O 2 (Holtappels et al, 2014). Using these new nanomolar techniques, in situ oxygen and respiration measurements derived from consumption of oxygen, showed that aerobic respiration occurs efficiently at extremely low oxygen concentrations (Tiano et al, 2014;Kalvelage et al, 2015;Garcia-Robledo et al, 2016). As well as the difficulty in measuring very low oxygen concentrations and rates of oxygen consumption, TABLE 1 | Recent midwater (100-1000 m) respiration estimates derived from dissolved oxygen consumption during a bottle incubation ( O 2 ), activity of the electron transport system (ETS), the reduction of the tetrazolium salt (INT), or the time resolved estimate of the amount of dissolved oxygen consumed since a water parcel was last in contact with the atmosphere, the oxygen utilization rate (OUR).…”
Section: Measurement Methodsmentioning
confidence: 71%
“…Such measurements would only be valid under the assumption that the process rates are not affected by the low concentration levels. However, this assumption seems reasonable, as values for the apparent half-saturation constant of the Michaelis-Menten equation (K m ) for microbial oceanic O 2 consumption have been shown to be in the nanomolar range (Tiano et al, 2014;Garcia-Robledo et al, 2016). Also, for compounds with a natural low ambient concentration and where a suitable microsensor exists, e.g., for nitrous oxide (N 2 O), SML microprofiling can likely be used to determine reaction rates in situ.…”
Section: Limitations and Outlook For Future Studiesmentioning
confidence: 99%